2012
DOI: 10.1902/jop.2012.110461
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Evaluation of the Antibacterial Efficacy of Honey In Vitro and Antiplaque Efficacy in a 4‐Day Plaque Regrowth Model In Vivo: Preliminary Results

Abstract: Honey has antibacterial action against tested oral microorganisms and also has antiplaque action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 44 publications
2
18
0
2
Order By: Relevance
“…A few clinical studies have reported reduction in plaque accumulation and gingival bleeding [26, 30] and decreased proportion of mutans streptococci [31] with application of honey intraorally, supporting the use of honey as an oral antimicrobial agent. Thus, the present preclinical study assessed the potential for subgingival application of manuka honey in the treatment of periodontal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A few clinical studies have reported reduction in plaque accumulation and gingival bleeding [26, 30] and decreased proportion of mutans streptococci [31] with application of honey intraorally, supporting the use of honey as an oral antimicrobial agent. Thus, the present preclinical study assessed the potential for subgingival application of manuka honey in the treatment of periodontal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In an in vitro study it was shown that chlorhexidine acts more antibacterial than honey [48]. However, the addition of honey or its components as natural products to mouth rinses, tooth pastes may be discussed as a beneficial option in prevention and therapy of periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…We used a non-brushing model that allowed for dental plaque accumulation that has been widely used to evaluate the effects of various mouthrinses [ 19 22 , 26 28 ]. Conducted in the absence of mechanical oral hygiene, the method provides direct evidence of the chemical action of formulations against plaque growth [ 29 ].…”
Section: Discussionmentioning
confidence: 99%